Factors Affecting the Uptake of Pay TV among Nairobi Residents in Kenya - Kimani , Edwin; Iravo , Mike (Journal of Marketing Studies, 2022)
Purpose: This study sought to find out the factors affecting the uptake of pay TV with a focus on Nairobi residents. The specific objectives of the study were to find out how cost implications, perceived satisfaction, awareness and reliable service provision affect the uptake of pay TV among Nairobi residents. Methodology: The study adopted a descriptive research design. The study used convenience sampling methods to select a sample size of 43 respondents from 50% of Nairobi Wards. The data collection instrument used was a structured questionnaire with both close and open-ended questions. The data collected was analyzed using SPSS and presentations made in tables, for easy interpretation. Results: Correlation analysis, established the existence of positive and significant relationship between effect of cost implications, perceived satisfaction, effect of pat TV awareness and effect of reliable service provision on the uptake of pay TV services among the residents of Nairobi. The study concludes that cost implications, pay TV awareness, perceived satisfaction, and reliable service provision are all key factors that are affecting the uptake of pay TV services among the residents of Nairobi. Unique Contribution to Theory and Practice: The study recommends that Pay TV service providers should enhance consumer education as far as pay TV versus free-to-air services is concerned. The study recommends that further research be carried out on the moderating effect of social media platforms (as alternates for broadcast media) on consumer choices for pay TV service